Ethoxyquin Inhibits the Progression of Murine Ehrlich Ascites Carcinoma through the Inhibition of Autophagy and LDH - Fekria Tayel; Magdy E. Mahfouz; Afrah F. Salama; Mohammed A. Mansour (Biomedicines, 2021)
Cancer cells exhibit an increased glycolysis rate for ATP generation (the Warburg effect) to sustain an increased proliferation rate. In tumor cells, the oxidation of pyruvate in the Krebs cycle is substituted by lactate production, catalyzed by LDH. In this study, we use ethoxyquin (EQ) as a novel inhibitor to target LDH in murine Ehrlich ascites carcinoma (EAC) and as a combination therapy to improve the therapeutic efficacy of the conventional chemotherapy drug, cisplatin (CIS). We investigated the anti-tumor effect of EQ on EAC-bearing mice and checked whether EQ can sustain the anti-tumor potential of CIS and whether it influences LDH activity. Treatment with EQ had evident anti-tumor effects on EAC as revealed by the remarkable decrease in the expression of the anti-apoptotic gene Bcl-2 and by a significant increase in the expression of apoptotic genes (BAX and caspase-3). EQ also caused a significant decrease in the autophagic activity of EAC cells, as shown by a reduction in the fluorescence intensity of the autophagosome marker. Additionally, EQ restored the altered hematological and biochemical parameters and improved the disrupted hepatic tissues of EAC-bearing mice. Co-administration of EQ and CIS showed the highest anti-tumor effect against EAC. Collectively, our findings propose EQ as a novel inhibitor of LDH in cancer cells and as a combinatory drug to increase the efficacy of cisplatin. Further studies are required to validate this therapeutic strategy in different cancer models and preclinical trials.